Liberty and Form in La amortajada, by María Luisa Bombal - Hosiasson, Laura Janina (2024)
Since its first publication in 1938, many of the dimensions of La amortajada have been assiduously studied, from its formal aspects, through its relationship with surrealism and the dissolution of the boundaries between reality and unreality, up to feminist approaches. In this essay we return to an approach that first privileges its execution, in order to verify how Bombal faced the structural challenges of this project. It is particularly interesting to verify how the erotic element organizes a large part of the design of this narrative, which can be read as a libertarian appeal within the socially conservative context of the 1930s. Finally, I intend to advance in the projections that this proposal acquires within the Latin American literary archive.